Improving the Role of Financial and Business Activity of Enterprises - Akhmedova A. T. (Researchparks Publishing, 2021)
The article is devoted to the study and characterization of the problems of financial and business activity of enterprises, as well as the search for measures related to improving the efficiency of resource use.